Kekuatan dan Batas Judicial Review dalam Arsitektur Hukum Indonesia - Mursyidi, Mursyidi (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2025)
The 1945 Constitution of the Republic of Indonesia grants judicial review authority to two state institutions: the Constitutional Court and the Supreme Court. However, the dualism of this authority has led to potential legal problems in its implementation, both conceptually and practically. This study aims to analyze the mechanism of judicial review within Indonesia’s legal system and to evaluate its effectiveness and consistency in upholding constitutional supremacy. The research employs a normative legal method with statutory, conceptual, historical, and comparative approaches. The findings reveal that the division of judicial review powers between the Constitutional Court and the Supreme Court creates inefficiencies and the possibility of inconsistent rulings. Additionally, there is ambiguity in the delineation of authority, which may lead to institutional conflicts and weaken constitutional oversight. Based on these findings, the study recommends a restructuring of the judicial review system in Indonesia by consolidating the authority under a single institution—the Constitutional Court. This consolidation is expected to strengthen constitutional oversight, ensure legal certainty, and enhance the effectiveness of the national legal system. The main contribution of this research lies in providing a conceptual and juridical basis for reinforcing the role of the Constitutional Court as the sole authority for judicial review, thereby promoting a more coherent, responsive, and constitutionally grounded legal order in Indonesia